2012
DOI: 10.1083/jcb.201206143
|View full text |Cite
|
Sign up to set email alerts
|

Noncentrosomal microtubules and type II myosins potentiate epidermal cell adhesion and barrier formation

Abstract: Noncentrosomal microtubules recruit myosin II to the cell cortex in order to engage adherens junctions and increase tight junction formation, resulting in an increase in mechanical integrity of cell sheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
90
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(105 citation statements)
references
References 39 publications
14
90
1
Order By: Relevance
“…It is known that microtubules regulate, and are regulated by, points of cell-cell contact (Chausovsky et al, 2000;Waterman-Storer et al, 2000;Yap and Manley, 2001;Ligon and Holzbaur, 2007), raising the possibility that microtubule network organisation is regulated at the supracellular or tissue level, as has recently been shown for the actomyosin system (Martin et al, 2009;Rauzi et al, 2010). However, there are a number of in vivo contexts where the ablation of microtubules was reported to have little influence on adherens junctions (Jankovics and Brunner, 2006;Brodu et al, 2010;Sumigray et al, 2012), indicating that the role of microtubules in tissue-shaping remains unclear.…”
Section: Introductionmentioning
confidence: 91%
“…It is known that microtubules regulate, and are regulated by, points of cell-cell contact (Chausovsky et al, 2000;Waterman-Storer et al, 2000;Yap and Manley, 2001;Ligon and Holzbaur, 2007), raising the possibility that microtubule network organisation is regulated at the supracellular or tissue level, as has recently been shown for the actomyosin system (Martin et al, 2009;Rauzi et al, 2010). However, there are a number of in vivo contexts where the ablation of microtubules was reported to have little influence on adherens junctions (Jankovics and Brunner, 2006;Brodu et al, 2010;Sumigray et al, 2012), indicating that the role of microtubules in tissue-shaping remains unclear.…”
Section: Introductionmentioning
confidence: 91%
“…These microtubules allow the transport machinery to deliver cilial regulatory proteins, and they promote cadherin clustering to maintain cell-cell junctions through the plus-end-binding protein CLIP170, and recruit myosin II for mechanical integrity at tight junctions (Bellett et al, 2009;Stehbens et al, 2006;Sumigray et al, 2012). However, the majority of the microtubules in epithelial cells are non-centrosomal and are aligned along the apical-basal axis, with their plus-ends orientated towards the basolateral membrane (Lüders and Stearns, 2007).…”
Section: Integrin-dependent Microtubule Dynamics Control Apical-basalmentioning
confidence: 99%
“…We focused on adherens junctions because they are important for elongation (Costa et al, 1998;Pasti and Labouesse, 2014) and prior work has suggested a functional link between microtubules and adherens junctions (Stehbens et al, 2006;Meng et al, 2008;Bellett et al, 2009;Huang et al, 2011;Sumigray et al, 2012;Revenu et al, 2014). Examination of E-cadherin/HMR-1::GFP (Achilleos et al, 2010) revealed fragmentation of the cadherin-based junctional complex in 38% of noca-1(RNAi) and 66% of spas OE embryos (Fig.…”
Section: Epidermal Microtubules Promote E-cadherin Clustering and Turmentioning
confidence: 99%
“…This result is also consistent with the observation that MLC-4 (DD) is unable to rescue let-502(sb118ts) mutants, suggesting that MLC-4 is not the only target of LET-502 (Gally et al, 2009). In cell culture, perturbing microtubules impacts myosin II accumulation at cell-cell contacts (Stehbens et al, 2006;Sumigray et al, 2012), prompting us to examine MLC-4::GFP distribution in spas OE embryos (Gally et al, 2009). However, microtubule degradation had no apparent effect on MLC-4::GFP localization, and it was not enriched at junctions (Fig.…”
Section: Perturbation Of Epidermal Microtubules Leads To Mild Elongatmentioning
confidence: 99%